Creating and Consuming Metadata from Transcribed Historical Vital Records for Ingestion in a Long-Term Digital Preservation Platform - DEBRUYNE, CHRISTOPHE (Springer, 2015)
In the Iri sh Record Linkage 1864 - 1913 (IRL) project, digital arch i- vists transcribe digitized register p ages containing vital records into a database, which is then used to generate RDF triples. H istorians then use those triples to answer some specific research quest ions on the IRL platform. Though the tr i- ples themselves are a highly valuable asset that can be adopted by many, the digitized records and their RDF representations need to be adequately stored and preserved according to best standards and guidelines to en sure those do not get lost over time. This was a problem currently not investigated within this project. This paper reports on the creation of Qualified Dublin Core from those triples for inge st ion with the digitized register pages in an adequate long - term digital preservation platform and repository. Rather than creating RDF only for the purpose of this project, we demonstrate how we can distill artifacts from the RDF that is fit for discovery, access, and even reuse via that repository and how we elicit and conserve the knowledge and memories about Ireland, its history and culture contained in those register pages
On the Move to Meaningful Internet Systems: OTM 2015 Workshops
PUBLISHED
Rhodes, Greece
Keywords: Vital Records; Mapping; Metadata; Linked Data; Intelligent Content & Communications; Linked Data; Mapping; Metadata; Vital Records